AN ASSESSMENT OF THE FACTORS THAT SHAPED ELECTORAL VIOLENCE IN 2019 BAYELSA STATE GUBERNATORIAL ELECTION - Otu, Onu Emmanuel; Odalonu, Boris Happy (African Journal of Social and Behavioural Sciences, 2021)
This study examined election and electoral violence in Nigeria with special focus on the 2019 Bayelsa State Gubernatorial Election. The purpose of the study was premised on examining the factors that influenced electoral violence in 2019 gubernatorial election in Bayelsa, to bring to fore the impacts of electoral violence on Bayelsan electorates in 2019 gubernatorial election and to suggest ways to curb or reduce electoral violence in Bayelsa State. The Zero-Sum game theoretical framework was found very suitable. In addition, the study reviewed scholarly works on issues related to the focus of the study. The study adopted ex-post facto research design and data for the study were gathered from secondary sources such as journals, magazines, text books, newspapers and materials relating to election and electoral violence in Nigeria. A combination of simple descriptive-analytical and deductive methods was mainly employed to analyze the data while inferences were drawn from writings and commentaries of other scholars. The study deduced that the leading causes of electoral violence before, during and after the 2019 Bayelsa gubernatorial election were violent acts of various cult groups, high level of insecurity, Godfatherism and unlawful acts of party agents. Based on the findings, the following recommendations were made, its imperative to amend the electoral law, adequate political education and socialization should be carried to the electorates and provision of adequate security to trouble spots as a way to curb electoral violence in Bayelsa State and Nigeria at large.